Water/MWCNT nanofluid based cooling system of PVT: Experimental and numerical research - Nasrin, Rehena; Rahim, Nasrudin Abd; Fayaz, Hussain; Hasanuzzaman, Md. (Elsevier, 2018)
In this research, an indoor experiment has been carried out of a PV module under controlled operating conditions and parameters. A novel design of thermal collector has been introduced, a complete PVT system assembled and water/MWCNT nanofluid used to enhance the thermal performance of PVT. An active cooling for PVT system has been maintained by using a centrifugal pump and a radiator have been used in the cycle to dissipate the heat of nanofluid in the environment to maintain proposed inlet temperature. 3D numerical simulation has been conducted with FEM based software COMSOL Multiphysics and validated by an indoor experimental research at different irradiation level from 200 to 1000 W/m2, weight fraction from 0 to 1% while keeping mass flow rate 0.5 L/min and inlet temperature 32 °C. The numerical results show a positive response to the experimental measurements. In experimental case, percentage of enhanced PV performance is found as 9.2% by using water cooling system. Higher thermal performance is obtained as approximately 4 and 3.67% in numerical and experimental studies, respectively by using nanofluid than water. In the PVT system operated by nanofluid at 1000 W/m2 irradiation, the numerical and experimental overall efficiency are found to be 89.2 and 87.65% respectively.